1982
DOI: 10.1002/lary.1982.92.6.650
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillar Hypertrophy and Upper Airway Obstruction in Evolutionary Perspective

Abstract: Primary care physicians have become increasingly reluctant to refer children for tonsillectomy and adenoidectomy (T and A) during the past years while antimicrobial therapy for pharyngotonsillitis and otitis media has become more common. Consequently, more children retain tonsils and adenoids throughout the childhood years. Airway compromise from adenotonsillar hypertrophy is reported in 11 cases — 8 with insidious onset, 3 with acute onset. Typical symptoms occurring during sleep include snoring, snorting, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…[2][3][4] It has been recently suggested that treatment with antibiotics 5 or with topical steroids 6 can decrease the severity of symptoms, but it has not been established whether medical treatment can also decrease the frequency of adenotonsillectomy. We report here the results of a controlled study that investigated the long-term effects of the use of nasal beclomethasone among children affected by adenotonsillar hypertrophy.…”
mentioning
confidence: 99%
“…[2][3][4] It has been recently suggested that treatment with antibiotics 5 or with topical steroids 6 can decrease the severity of symptoms, but it has not been established whether medical treatment can also decrease the frequency of adenotonsillectomy. We report here the results of a controlled study that investigated the long-term effects of the use of nasal beclomethasone among children affected by adenotonsillar hypertrophy.…”
mentioning
confidence: 99%
“…During sleep, inspiratory collapse of the upper airway can occur. This is due to the negative intraluminal pressure exceeding the force of the dilatory muscles of the pharynx, which in turn is due to either anatomical or pathophysiological factors [16,[19][20][21].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The recognition of the association between adenotonsillar hypertrophy and OSA syndrome has led to an increasing number of children presenting for adenotonsillectomy with this syndrome in the USA and Europe [20]. A retrospective survey of adenotonsillectomies at the Mt Sinai Medical Center found that in 1978 all 282 operations were for recurrent infection.…”
Section: Managementmentioning
confidence: 99%
“…The development of effective antibiotics has led to a decrease in the number of adenotonsillectomies in children but to a subsequent increase in the number of children with severe tonsillar problems [2], Hypoventilation secondary to snoring or sleep apnea syndrome impairs oxygen transport to the peripheral organs and causes hypoxia, CCU retention, growth retardation and impaired physical and psychologi cal status. Pulmonary hypertension and cor pulmonale may develop in a small number of these children [3], and it has been reported that symptoms and signs of upper airway obstruction during sleep might be alleviated after adenotonsillectomy [4][5][6],…”
Section: Introductionmentioning
confidence: 99%
“…Snoring or obstructive sleep apnea syndrome (OSAS) may be caused by partial or complete obstruction of the upper airway during sleep [1], The main cause of snoring or sleep apnea syndrome in children is tonsillar hypertro phy and/or adenoid vegetation [2]. The development of effective antibiotics has led to a decrease in the number of adenotonsillectomies in children but to a subsequent increase in the number of children with severe tonsillar problems [2], Hypoventilation secondary to snoring or sleep apnea syndrome impairs oxygen transport to the peripheral organs and causes hypoxia, CCU retention, growth retardation and impaired physical and psychologi cal status.…”
Section: Introductionmentioning
confidence: 99%